The Effect of Remittances on Labour Supply in the Republic of Haiti - Jadotte, Evans; Ramos, Xavier (Taylor and Francis, 2016)
We examine the labor supply effect of remittances in the Republic of Haiti, the prime international remittances recipient country in the Latin American and Caribbean (LAC) region relative to its GDP. Unlike previous empirical literature we address three econometric issues that may bias the estimates. We account for endogeneity of the remittances with respect to labor supply, for the zero-inflated nature of our dependent variable, hours of work, and for the self-selection of the migrant sample. Our results are in line with previous literature, and point to a decline of labor supply in the presence of remittances. However, contrary to previous findings, the labor market response to remittances of female household heads is not as sensitive as male’s.